Chemistry and Pharmaceutical Applications of Excipients Derived from Tamarind - Rasala, T.M.; Kale, V.V.; Lohiya, G.K.; Moharir, K.S.; Ittadwar, A.M.; Awari, J.G. (Asian Journal of Chemistry, 2010)
Drug dosage forms contain many components in addition to the active pharmaceutical ingredient(s) to assist in the manufacturing process as well as to optimize drug delivery. Due to advances in drug delivery technology, excipients are currently included in novel dosage forms to fulfill specific functions and in some cases they directly or indirectly influence the extent and/ or rate of drug release and absorption. Excipients have been successfully employed in the formulation of solid, liquid and semi-solid dosage forms and are specifically useful in the design of modified release drug delivery systems. Synthetic natural polymers and excipients have been investigated extensively for this purpose, but the use of natural excipients for pharmaceutical applications is attractive because they are economical, readily available, non-toxic, capable of chemical modifications, potentially biodegradable and with few exceptions, and also biocompatible. Of increasing importance is the fact that plant resources are renewable and if cultivated or harvested in a sustainable manner, they can provide a constant supply of raw material. Traditionally, excipients were included in drug formulations as inert vehicles that provided the necessary weight, consistency and volume for the correct administration of the active ingredient, but in modern pharmaceutical dosage forms they often fulfill multi-functional roles such as improvement of the stability, release and bioavailability of the active ingredient, enhancement of patient acceptability and performance of technological functions that ensure ease of manufacture. This mini review discusses the chemistry and potential use of substances derived from Tamarind as multifunctional excipient in various pharmaceutical dosage forms.